1990
DOI: 10.1152/jappl.1990.69.2.532
|View full text |Cite
|
Sign up to set email alerts
|

Fractal properties of pulmonary blood flow: characterization of spatial heterogeneity

Abstract: The heterogeneity of pulmonary blood flow was examined using a fractal analytic procedure, and the results were compared with the traditional gravitational model of flow distribution. 99mTc-labeled macroaggregate was injected intravenously at functional residual capacity in six supine anesthetized dogs. The lungs were fixed in situ and sliced in transverse sections. The slices were imaged on a planar gamma camera, and a three-dimensional array of blood flow measurements was reconstructed for each lung. Fractal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
140
1
2

Year Published

1997
1997
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(153 citation statements)
references
References 0 publications
10
140
1
2
Order By: Relevance
“…Inspired by a demonstration of scale-dependent heterogeneity of cardiac blood flow (5, 37), a high-resolution study of lung perfusion distribution confirmed that the spatial heterogeneity of regional blood flow increased in a similar predictable fashion as resolution was enhanced (25). This scale dependence of measured regional blood flow heterogeneity can be understood as a consequence of the progressive branching of the pulmonary arterial tree, where flows will be heterogeneous but locally correlated.…”
Section: Scale-dependent Heterogeneity Of Lung Blood Flowmentioning
confidence: 83%
See 1 more Smart Citation
“…Inspired by a demonstration of scale-dependent heterogeneity of cardiac blood flow (5, 37), a high-resolution study of lung perfusion distribution confirmed that the spatial heterogeneity of regional blood flow increased in a similar predictable fashion as resolution was enhanced (25). This scale dependence of measured regional blood flow heterogeneity can be understood as a consequence of the progressive branching of the pulmonary arterial tree, where flows will be heterogeneous but locally correlated.…”
Section: Scale-dependent Heterogeneity Of Lung Blood Flowmentioning
confidence: 83%
“…Nicolaysen et al (45) used circumferentially cut sections from partially inflated and frozen RMS-labeled lungs to refute the existence of a significant radial gradient of flow in the lung. After intravenous injection of a flow label, Glenny and Robertson (25) employed in situ supine tissue fixation and acquired gamma camera images of transverse slices of the fixed lung. Regardless of the approach to fixation, sectioning, and counting, the regional flow heterogeneity attained by these studies revealed coefficients of variation ranging between 20 and 45%.…”
Section: Methods To Create Microsphere Maps Of Flowmentioning
confidence: 99%
“…In the pulmonary circulation literature, these slopes are described in terms of fractal dimensions because a fractal system can be described by using multiscale analysis (7). The fractal dimension is equal to one minus the slope of the regression line (5). Thus a slope of Ϫ0.5 has a fractal dimension of 1.5, which corresponds to a condition in spatial statistics known as complete spatial randomness (CSR; Ref.…”
Section: Analysis Of Particle Distributionmentioning
confidence: 99%
“…Glenny and Robertson considered this question and predicted how the CV of blood flow should behave as the tissue subdivision volume approached what they described as "the anatomic limit of the capillary" (5). At such a volume, they predicted that blood flow would become uniform among lung units, producing a fractal plot that was horizontal (fractal dimension 1.0) as it extended leftward through smaller and smaller tissue subdivision volumes.…”
Section: Particle Distribution Analysismentioning
confidence: 99%
See 1 more Smart Citation